Analysis for Feasibility of Spitzer's Schemes Complication for Spacecraft Final Insertion into Geostationary Orbit by Electric Propulsion. (2017) - Konstantinov, Mikhail; Svotina, Victoria
Abstract: In the mid-90s of the past century Arnon Spitzer offered a flight scheme comprising an elliptical synchronous equatorial orbit for the SC injection into geostationary orbit (GEO). The advantages of such scheme were related to the SC control simplicity during its transfer from the elliptical synchronous orbit into GEO. The main advantage of Spitzer's scheme is the possibility of observing spacecraft from Earth using a limited number of ground stations along the entire trajectory of the SC flight from an intermediate orbit into GEO. Some flight schemes, which preserve the main advantage of the Spitzer's scheme, are analyzed. The inclination and the eccentricity of the intermediate synchronous orbit are optimized. Several variants of the yaw angle control are analyzed. Numerical analysis was carried out for a space transportation system based on the launch vehicle "Angara-A5", chemical upper stage "KVTK", and electric propulsion system comprising four thrusters SPD-140 with the specific impulse of 1700 s.